Nominal Phrase Structure in Indonesian: A Study of Generative Grammar - Alpiani Lubis; Immanuel Silaban; Eka Silviana Siregar; Juwita Paramita Tampubolon; Doan Yohannes Manullang (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Nominal phrases are an important syntactic element because they function as the core of clauses and sentences. This study aims to analyze the structure of nominal phrases in Indonesian using a generative grammar approach. Through the X-Bar theoretical framework in generative grammar, this study describes how nominal phrases are formed from lexical categories (N) that can be expanded by adding determinants (D), adjuncts, or complements. Research data were obtained from written texts in the form of news articles, scientific works, and popular literature to show variations in the use of nominal phrases in different contexts. Research data were collected using instruments such as Written Data Documentation Sheets, Nominal Phrase Identification and Extraction Sheets, X-Bar Structure Annotation Tables, Coding and Categorization Guidelines, and Analysis Notes. The analysis shows that Indonesian nominal phrases have a hierarchical structure with a phrase head (N) that can be expanded to the left or right. The existence of determinants, adjectival phrases, prepositional phrases, and relative clauses shows a complex transformation process, but remains consistent with the principles of generative grammar. The results of this study confirm that generative theory is effective in explaining the regularity and universality of Indonesian nominal phrase structures. Thus, this research contributes to the development of syntactic studies and provides a deeper understanding of how Indonesian represents syntactic relations within the framework of universal grammar.